2004
DOI: 10.4049/jimmunol.173.2.1406
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role of MD-2 in TLR4-Dependent Signaling during Helicobacter pylori-Associated Gastritis

Abstract: TLR4, a member of pattern recognition receptors, is the main receptor of LPS. MD-2 physically associates with TLR4 on the cell surface and confers LPS responsiveness. Helicobacter pylori LPS is one of the major virulence factors for induction of gastritis. We demonstrated in this study the role of MD-2 in TLR4-dependent signaling in H. pylori-associated gastritis. Gastric biopsy samples collected from patients with and without H. pylori infection and four gastric cancer cell lines were used for this study. TLR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
138
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(148 citation statements)
references
References 67 publications
(49 reference statements)
7
138
1
2
Order By: Relevance
“…32 Moreover, Su et al 33 indicated that H. pylori activates TLR4 expression in epithelial cells. Similarly, Ishihara et al 34 showed that LY96 expression was elevated in gastric epithelial cells during H. pylori infection and they proposed that the TLR4/MD-2 system is an important receptor complex involved in the response to H. pylori LPS in the stomach. Interestingly, we found that many chemokines were upregulated in infected patients, mainly in the antrum.…”
Section: Discussionmentioning
confidence: 93%
“…32 Moreover, Su et al 33 indicated that H. pylori activates TLR4 expression in epithelial cells. Similarly, Ishihara et al 34 showed that LY96 expression was elevated in gastric epithelial cells during H. pylori infection and they proposed that the TLR4/MD-2 system is an important receptor complex involved in the response to H. pylori LPS in the stomach. Interestingly, we found that many chemokines were upregulated in infected patients, mainly in the antrum.…”
Section: Discussionmentioning
confidence: 93%
“…2,[4][5][6] For example, CDX2 expression was reportedly upregulated in cultured epithelial cells when they were infected with bacteria, and interactions of TLR with microbial components are involved in the regulation of MUC expression. [30][31][32][33][34][35] Therefore, bacterial components in bile may induce CDX2 expression and then aberrant MUC2 expression in the ducts.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, preincubation with anti-TLR4 antibody or anti-TLR2 antibody downregulated CDX2 and MUC2 expression in BECs induced by LPS (a ligand for TLR4) or Pam3 (a ligand for TLR2), respectively, Interaction of TLR with PAMPs is known to activate intracellular signals followed by NF-kB translocation and the synthesis of molecules including inflammatory cytokines. 24,35 The involvement of TLR2 and/or TLR4 in Helicobacter pylori infections has been revealed in cultured gastric epithelial cell lines, 33,34 in which MUC2 was induced to express by TLR2/ bacterial components and the activation of NF-kB. 3,31,32 PAMPs-induced CDX2 and MUC2 overexpression via an NF-kB pathway located downstream of TLRs.…”
Section: Intestinal Metaplasia Of Bile Ducts H Ikeda Et Almentioning
confidence: 99%
“…TLR4 and MD-2 have been found to be expressed at significantly higher levels in gastric mucosa. This indicates the possible role of TLR4/MD-2 complex in host response to H. pylori derived LPS (Ishihara et al, 2004). Interestingly, TLR5 and TLR9 are located on both apical surface and basolateral surface but during H. pylori infection, these TLRs are not found to be expressed at the apical surface (Schmausser et al, 2005).…”
Section: Tlrs In Infectious Diseasesmentioning
confidence: 86%